2003
DOI: 10.1108/02686900310482650
|View full text |Cite
|
Sign up to set email alerts
|

Credibility and expectation gap in reporting on uncertainties

Abstract: This paper analyzes and reports on studies that examine the extent to which international auditing boards have accomplished the goal of reducing the expectation gap in reporting on uncertainties. This is because there has been a long-running controversy between the auditing profession and the community of financial statement users concerning the responsibilities of the auditors to the users. Enron and WorldCom scandals have provoked the public to incite the government and professional bodies to impose stringen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 11 publications
(4 reference statements)
0
45
0
1
Order By: Relevance
“…The causes also include uncertainty in the nature of auditing [60], the consequence of self-regulation of auditing profession with little or no interference by government [52], the ignorance, misunderstanding, and unreasonable expectations of the users about audit functions [48]. In addition, Shaikh and Talha [64] stated that reasons for audit expectation gap include corporate failures that made the public to lose confidence in the audit process, the retrospection, evaluation of audit performance, and response time lag due to evolutionary development in auditor's role. Ruhnke and Schmidt [58] attribute the causes of audit expectation to exaggeration of the audit expectation gap by the public, inability of the public to accurately assess the performance of the auditors, deficiency in auditors' performance, and auditors are not fully aware of their responsibilities.…”
Section: Causes Of Audit Expectation Gapmentioning
confidence: 99%
“…The causes also include uncertainty in the nature of auditing [60], the consequence of self-regulation of auditing profession with little or no interference by government [52], the ignorance, misunderstanding, and unreasonable expectations of the users about audit functions [48]. In addition, Shaikh and Talha [64] stated that reasons for audit expectation gap include corporate failures that made the public to lose confidence in the audit process, the retrospection, evaluation of audit performance, and response time lag due to evolutionary development in auditor's role. Ruhnke and Schmidt [58] attribute the causes of audit expectation to exaggeration of the audit expectation gap by the public, inability of the public to accurately assess the performance of the auditors, deficiency in auditors' performance, and auditors are not fully aware of their responsibilities.…”
Section: Causes Of Audit Expectation Gapmentioning
confidence: 99%
“…The expectation gap has been attributed to many numbers of different causes: 1) the probabilistic nature of auditing; 2) the ignorance, naivety, misunderstanding and unreasonable expectations of non-auditors about the audit function; 3) The evaluation of audit performance based upon information or data not available to the auditor at the time the audit was completed; 4) The evolutionary development of audit responsibilities, which creates time lags in responding to changing expectations; 5) Corporate crises which lead to new expectations and accountability requirements; or 6) The profession attempting to control the direction and outcome of the expectation debate to maintain the status quo (Shaikh and Talha, 2003).…”
Section: The Sources and Componentsmentioning
confidence: 99%
“…Salehi et al (2009) investigated about auditor independence and audit expectation gap and reported that an independent auditor is important since the separation of ownership from the management; the independent factor is the foundation of the public accounting profession. Shaikh and Talha (2003) investigated different studies that test the extent to which international auditing boards had accomplished to reduce the expectation gap in reporting on uncertainties. This is due to the fact that there used to be a long-running controversy between the auditing profession and the community of financial statement users on the responsibilities of the auditors to the users.…”
Section: Introductionmentioning
confidence: 99%